Wanted: A Maine Woods Dialogue - Lapping, Mark (Maine Policy Review, 2007)
In his commentary on Jerry Bley’s article on the Maine Land Use Planning Commission (LURC), Mark Lapping discusses the need for serious dialogue about the future of the Maine North Woods. He believes that LURC’s mandate needs to be altered and enlarged